Trametinib Inhibits the Growth and Aerobic Glycolysis of Glioma Cells by Targeting the PKM2/c-Myc Axis - Gao, Mingjun; Yang, Jin; Gong, Hailong; Lin, Yuancai; Liu, Jing (Frontiers in Pharmacology, 2021)
Glioma is a primary tumor originated from glial progenitor cells. Traditional treatment methods, including surgery, radiotherapy and chemotherapy, have many limitations on the prognosis of glioma patients. Therefore, It is of great significance to find a drug that can effectively treat glioma at present. Trametinib can inhibit MAPK pathway and regulate its downstream extracellular related kinase. It has been widely used in the treatment of BRAF V600E mutant metastatic melanoma. Previous studies have found that trametinib can improve the prognosis of melanoma patients with brain metastasis. In this research, we found the therapeutic effects of trametinib on glioma in vivo and in vitro. We found that trametinib can inhibit proliferation, migration and invasion of glioma cells, and induce apoptosis of glioma cells. More importantly, trametinib can suppress the expression of PKM2 in glioma cells. We found that the above-mentioned inhibited cell biological behaviors and intracellular glycolysis levels were reversed by overexpressing the expression of PKM2 in glioma cells. We found that c-myc was also inhibited and c-myc could be increased after overexpression of PKM2. After PKM2 overexpressed and c-myc silenced, we found that the biological behaviors and glycolysis levels increased by PKM2 overexpression were reversed again. And these inhibitory effects also appeared in vivo. Trametinib inhibited the growth of glioma cell transplanted tumor, and overexpression of PKM2 and silence of c-myc could reverse the inhibition of trametinib on the growth of transplanted tumor. To sum up, these experimental results show that trametinib may inhibit the growth and intracellular glycolysis of glioma cells by targeting PKM2/c-myc pathway.